Attention Economy: Smartphone dan Media Sosial Candu Manusia Modern? - Siti Reni; Masduki Asbari; Mohamad Biazt Ramadhan (Yayasan Aya Sophia Indonesia, 2024)
The aim of this study is to find out whether technology can make people addicted to smartphones or social media in this day and age. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Kamino YouTube Channel entitled